A surgical model of short bowel syndrome induces a long-lasting increase in pancreatic beta-cell mass - Pérez-Arana, Gonzalo; Camacho-Ramírez, Alonso; Segundo-Iglesias, M Carmen; Lechuga-Sancho, Alfonso M; Sancho-Maraver, Eva; Aguilar-Diosdado, Manuel; Prada-Oliveira, José Arturo (Histology and histopathology, 2015)
Several surgical techniques are used nowadays as a severe treatment for obesity and diabetes mellitus type 2. These techniques are aggressive due to drastic changes in the nutrient flow and non-reversible modifications on the digestive tube. In this paper we present the effects of a massive intestinal resection on the pancreas. Results have shown that short bowel technique is less aggressive to normal anatomy and physiology of the intestinal tract than Gastric bypass or biliopancreatic diversion (e.g.). In this paper we reproduce a model of short bowel syndrome (SIC), with similar surgical conditions and clinical complications as seen in human cases. This work was conducted on normal Wistar rats, with no other concurrent factors, in order to determine the effects on normal pancreas islets. We measured pancreatic implications by histomorphometric studies, which included beta-cell mass by immunocytochemistry, and apoptosis/proliferation test with TUNEL technique and Ki-67. Briefly, we reported on an increased relative area of the islets of the pancreas, as well as an increase in the average size of islets in the SIC versus the control group. Furthermore we stated that this increase in size of the pancreatic islets is due to the mechanisms of proliferation of beta cells in animals undergoing SIC. These goals could reveal a direct influence of surgical modification of the digestive tract over the pancreatic beta cell homeostasis. In this sense, there are many potential stimulators of intestinal adaptation, including peptide hormones and growth components which are associated or involved as effectors of the endocrine pancreas.